1.8-kV circular AlGaN/GaN/AlGaN double-heterostructure high electron mobility transistor *Project supported by the National Key Research and Development Program of China (Grant No. 2016YFB0400100), the National Natural Science Foundation of China (Grant Nos. 11435010, 61474086, and 61804125), and the Natural Science Basic Research Program of Shaanxi Province, China (Grant No. 2016ZDJC-02). (February 2019) - Zhao 赵, Sheng-Lei 胜雷; Wang 王, Zhi-Zhe 之哲; Chen 陈, Da-Zheng 大正; Wang 王, Mao-Jun 茂俊; Dai 戴, Yang 扬; Ma 马, Xiao-Hua 晓华; Zhang 张, Jin-Cheng 进成; Hao 郝, Yue 跃
Abstract: In this paper, we present a 1.8-kV circular AlGaN/GaN/AlGaN double-heterostructure high electron mobility transistor (DH HEMT) with a gate-drain spacing L GD = 18.8 μ m . Compared with the regular DH HEMT, our circular structure has a high average breakdown electric-field strength that increases from 0.42 MV/cm to 0.96 MV/cm. The power figure of merit V BR 2 / R ON for the circular HEMT is as high as 1.03 × 10 9 V 2 · Ω − 1 · cm − 2 . The divergence of electric field lines at the gate edge and no edge effect account for the breakdown enhancement capability of the circular structure. Experiments and analysis indicate that the circular structure is an effective method to modulate the electric field.